The Influence of Organic Breastfeeding Doses, Waste of Pig and Waste of Sheep. The Growth of The Life of The (Syzygium Malaccense) - Araujo, Maria de; Martins, Romaldo; Miguel, Julião (Arbain Publishing, 2025)
In general, green plants are planted in the field but a plant type, such as a plant that is used to provide shelter in front of the house. The benefits of red beans are foods that are sweet and tasteful, when consumed as a traditional medicine or alternative medicine, contain a large amount of vitamin C in the fruit, and increase human resistance, among others. The specific objective of this research is to find out the influence of organic breastfeeding, interactions and optimal doses of organic breastfeeding of pigs waste and sheep waste on the growth of green plants. The hypothesis of this research is that the use of organic breastfeeding of Tean and different sheep waste can increase the growth of red Tean plants, in the interaction between organic manure and in the optimal dose of organic manure pigs for the growth of green manure plants. The research design used in this section of the research is Randomized block Design o there are 2 (two) factors. Treatment Form with a factorial model. The first factor is the treatment of the organic breastfeeding of pigs at the 4th level and the second factor is the treatment of the breastfeeding of sheep at the 4th level. Treatment is estimated at 16 treatment units. The combination of treatment will be Repeat the 3rd time so that 48 polybag treatment units are needed. Observation of the growth of the red The following are the data to be taken: A). While the green plant nursery, B). The quantity of green plant nursery C). The diameter of the green plant. The research results show that the application of organic breastfeeding of waste of pigs and waste of sheep can be increase the growth of green plants. Plantation in the Faculty of Agriculture Technology, UNPAZ Satelit Fields, Liquica Municipality. significant interactions for the growth of green plants for the treatment of organic breastfeeding doses of manure and organic breastfeeding waste of sheep. The application of the organic dose of breastfeeding of 200 gr and the application of the organic dose of breastfeeding of 150 gr, indicates that the dose is the best with good results.